2008
DOI: 10.1080/10253890701535160
|View full text |Cite
|
Sign up to set email alerts
|

Examination stress and components of working memory

Abstract: Previous research suggests that stress can influence a broad range of memory functions. In this study we investigated the effect of a naturalistic stressor, examination stress, on working memory in young adults. In order to accomplish this aim, participants were tested on psychological and hormonal measures of stress and on Digit Span, once during a low stress period and once during a high stress period. The high examination stress condition was associated with an increase in cortisol and subjective impression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
4
29
2
Order By: Relevance
“…Nonetheless, our findings are consistent with the animal work of Wood and Shors (Wood and Shors, 1998) who demonstrated that associative learning, supported by brain regions that also contribute to working memory (Kronforst-Collins and Disterhoft, 1998), benefits from stress in the absence of estradiol or from estradiol in the absence of stress but under conditions of estradiol plus stress, performance deteriorates. Elevated stress hormone-related enhancements in working memory, a task that benefits from increased arousal (Lewis, et al, 2008), have also been reported by others (Cornelisse, et al, 2010; Weerda, et al, 2010; Yuen, et al, 2010). Estradiol increases HPA axis responsiveness to stress (Gupta, et al, 2001; Viau and Meaney, 2004; Weiser and Handa, 2009) and alters monoaminergic activity in prefrontal brain circuits affecting arousal and cognitive function (Jacome, et al, 2010; Luine, et al, 1998).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Nonetheless, our findings are consistent with the animal work of Wood and Shors (Wood and Shors, 1998) who demonstrated that associative learning, supported by brain regions that also contribute to working memory (Kronforst-Collins and Disterhoft, 1998), benefits from stress in the absence of estradiol or from estradiol in the absence of stress but under conditions of estradiol plus stress, performance deteriorates. Elevated stress hormone-related enhancements in working memory, a task that benefits from increased arousal (Lewis, et al, 2008), have also been reported by others (Cornelisse, et al, 2010; Weerda, et al, 2010; Yuen, et al, 2010). Estradiol increases HPA axis responsiveness to stress (Gupta, et al, 2001; Viau and Meaney, 2004; Weiser and Handa, 2009) and alters monoaminergic activity in prefrontal brain circuits affecting arousal and cognitive function (Jacome, et al, 2010; Luine, et al, 1998).…”
Section: Discussionsupporting
confidence: 65%
“…Although chronic stress typically impairs episodic memory (Lupien, et al, 2005; Schwabe and Wolf, 2010), acute stress can be harmful or beneficial for executive control abilities depending on the specific demands of the task. Increasing stress can enhance performance on tasks of working memory that benefit from increased arousal, yet have a detrimental effect when there are additional attentional demands such as efficient filtering of irrelevant information or set shifting (Lewis, et al, 2008; Liston, et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Working memory is considered to be a critical component or correlate of EF (Scheres et al, 2004; Willcutt, Pennington, Olson, Chhabildas, & Huslander, 2005c). Digits Forward is thought to involve rehearsal of the contents of working memory; Digits Backward likely involves the additional component of manipulation or sequencing (e.g., Lewis, Nikolova, Chang, & Weekes, 2008). Split-half reliabilities average .85 across the age span of the standardization sample (Wechsler, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Through ascending projections from brainstem nuclei where the locus coeruleus norepinephrine and midbrain dopaminergic systems locate, these stress-sensitive catecholamines alter neuronal functioning of widely distributed brain regions, particularly including the PFC (Arnsten and Li, 2005; Aston-Jones and Cohen, 2005; Arnsten, 2009; Sara, 2009). Converging evidence from human behavioral and neuroimaging studies have confirmed that acute stress indeed alters WM performance with both detrimental (Elzinga and Roelofs, 2005; Oei et al, 2006; Luethi et al, 2008; Schoofs et al, 2008) and enhancing (Lewis et al, 2008; Weerda et al, 2010; Hidalgo et al, 2011) effects, likely through altered efficiency of WM-related processing in dorsolateral PFC (Porcelli et al, 2008; Qin et al, 2009; Weerda et al, 2010). Interestingly, animal studies suggest that stress-sensitive catecholamines exert an inverted U-shaped influence on prefrontal functions (Aston-Jones and Cohen, 2005; Vijayraghavan et al, 2007), in which prefrontal functioning reaches an optimum at an intermediate level of catecholaminergic activity (Arnsten and Li, 2005; Aston-Jones and Cohen, 2005; Vijayraghavan et al, 2007).…”
Section: Introductionmentioning
confidence: 97%